Post-surgical Persistent Hyperparathyroidism Successfully Treated with Parathyroid Radiofrequency Ablation: A Case Report - Di Marco, Francesco; Cusini, Claudio; Ferrulli, Anna; Mauri, Giovanni; Luzi, Livio (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
BackgroundCurrently, parathyroidectomy is the standard treatment for Primary Hyperparathyroidism (PHPT). Surgical treatment is often effective, although not free of complications and relapses. Minimally invasive techniques, such as Microwave Ablation (MWA) and Radiofrequency Ablation (RFA), are an alternative to surgery in selected patients. We have, herein, reported on the successful use of RFA in a patient with post-surgical persistent hyperparathyroidism.Case PresentationA 54-year-old woman was referred to our Center for mild hypercalcemia with exams revealing Primary Hyperparathyroidism (PHPT). Neck ultrasound and Technetium-99 Methoxy-isobutyl-isonitrile (99mTc-MIBI) scintigraphy scanning revealed a suspicious right parathyroid hyperplasia/adenoma. She underwent parathyroidectomy and histological examination showed a parathyroid nodular hyperplasia. During the follow-up, she suffered from persistent hyperparathyroidism due to a left parathyroid hyperplasia. Thus she was treated with RFA. Blood tests after the procedure showed the remission of the disease 7 months post-treatment.ConclusionA minimally invasive technique for PHPT may represent a valid alternative to surgery, especially in patients with an elevated surgery-related risk. More studies are necessary to investigate the benefit of RFA as a first-line treatment in PHPT.
Keywords: minimally invasive technique